2021
DOI: 10.47162/rjme.62.1.24
|View full text |Cite
|
Sign up to set email alerts
|

Histopathological and immunohistochemical changes of the marginal periodontium in patients with Turner syndrome

Abstract: Turner syndrome (TS) is characterized by partial or complete loss of a sexual chromosome, resulting in an incomplete development of the body, gonadic failure, cardiac and renal abnormalities, oro-dental changes, etc. In our study, we proposed to perform a histological and immunohistochemical (IHC) study of the periodontium changes in patients with TS. The biological material under study was represented by fragments of gingival mucosa harvested from 18 patients with TS who presented advanced periodontal lesions… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 57 publications
0
5
0
Order By: Relevance
“…Connective tissue defects, such as cystic medial necrosis of the arterial wall, are common findings in postmortem examination of Turner syndrome with spontaneous artery dissection. This finding is relatively common in cases of Turner syndrome complicated by histology 6,12) . The arterial wall abnormalities in Turner syndrome are not restricted to the aorta.…”
Section: A a B B C C A A B Bmentioning
confidence: 79%
“…Connective tissue defects, such as cystic medial necrosis of the arterial wall, are common findings in postmortem examination of Turner syndrome with spontaneous artery dissection. This finding is relatively common in cases of Turner syndrome complicated by histology 6,12) . The arterial wall abnormalities in Turner syndrome are not restricted to the aorta.…”
Section: A a B B C C A A B Bmentioning
confidence: 79%
“…Recently, periodontal disease is a changed concept, no longer linked to a certain bacterium, but more to polymicrobial groups, these causing dysbiosis and modifying normal immune responses. It has been demonstrated that Porphyromonas gingivalis (a pathogen found in humans in the oral cavity), in small numbers (<1%) determines and modulates the virulence of the entire community [ 11 , 12 , 13 , 14 , 28 ]. Moreover, dysbiosis causes periodontitis and thus the subgingival microbiome is important in the pathogenesis of the disease and has been associated with systemic diseases, such as oral, esophageal, gastric, lung, pancreatic, prostate and breast cancer.…”
Section: Oral Microbiome In Mouth and Systemic Diseasesmentioning
confidence: 99%
“…Dental caries represents the leading cause of tooth and loss oral pain and could begin as small surface changes and continue until dentin is getting damaged. The accumulation of subgingival plaque leads to periodontal disease thus producing changes in the microbiota from a health to a disease [ 11 , 12 , 13 , 14 ]. Today, the treatment of periodontal disease consists in the reduction of the number of local pathogens to maintain disease control.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Recently, periodontal disease is a changed concept, no longer linked to a certain bacterium, but more to polymicrobial groups, these causing dysbiosis and modifying normal immune responses. It has been demonstrated that Porphyromonas gingivalis (a pathogen found in humans in the oral cavity), in small numbers (<1%) determines and modulates the virulence of the entire community [11][12][13][14]28].…”
Section: The Oral Dysbiosis In Dental Caries Periodontal Disease Oral...mentioning
confidence: 99%